2003
DOI: 10.1007/978-3-662-06508-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Dendritic Cells by Lymphocytic Choriomeningitis Virus

Abstract: Dendritic cells (DCs) comprise the major antigen-presenting cells (APCs) of the host, uniquely programmed to stimulate immunologically naïve T lymphocytes. Viruses that can target and disorder the function of these cells enjoy a selective advantage. The cellular receptor for lymphocytic choriomeningitis virus (LCMV), Lassa fever virus (LFV), and several other arenaviruses is α-dystroglycan (α-DG). Among cells of the immune system, CD11c + and DEC-205 + DCs primarily and preferentially express α-DG. By selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 62 publications
3
58
0
Order By: Relevance
“…In vitro studies of Ebola-Z virus revealed that suppression of immune responses can take place within infected cells (4,5,15,16,17) and that direct contact of virion particles with T cells can render them unresponsive (10). In addition, dendritic cells infected with Ebola-Z virus have been shown to be functionally impaired and are poor stimulators of T cells (24), as has also been described for measles virus (29,32) and lymphocytic choriomeningitis virus (33). Since dendritic cells are key components in adaptive immune responses, it is reasonable to assume that the degree to which these cells are infected or impaired has a direct impact on antigen processing and the recruitment and activation of effector cells.…”
Section: Effects Of Ebola-s Virus Infection On Blood Cells the Develmentioning
confidence: 90%
“…In vitro studies of Ebola-Z virus revealed that suppression of immune responses can take place within infected cells (4,5,15,16,17) and that direct contact of virion particles with T cells can render them unresponsive (10). In addition, dendritic cells infected with Ebola-Z virus have been shown to be functionally impaired and are poor stimulators of T cells (24), as has also been described for measles virus (29,32) and lymphocytic choriomeningitis virus (33). Since dendritic cells are key components in adaptive immune responses, it is reasonable to assume that the degree to which these cells are infected or impaired has a direct impact on antigen processing and the recruitment and activation of effector cells.…”
Section: Effects Of Ebola-s Virus Infection On Blood Cells the Develmentioning
confidence: 90%
“…Further studies in adult mice demonstrated that enhanced viral infiltration into the white pulp of the spleen was associated with increased binding to α-DG (152) and that clone 13 also more effectively targeted fibroblastic reticular cells resulting in decreased conduit function of the spleen (160). The disruption in splenic function (158,160), physical destruction of dendritic cells (161), and inhibition of dendritic cell differentiation and maturation (162,163) are likely contributors to the immunosuppression observed during clone 13 infection. More recently, it has also been revealed that inhibitory molecule such as PD-1 (164) and IL-10 (165) are upregulated early following clone 13 infection and also contribute to the immunosuppressive milieu.…”
Section: Lcmv Clone 13 and Chronic Infectionmentioning
confidence: 99%
“…It has been also demonstrated that chronic LCMV preferentially and persistently infects mDCs among DC populations (78). Therefore, the enhanced infection of DCs, followed by reduced T cell stimulatory capacity, is probably one of the mechanisms by which chronic pathogens initiate immunosuppression within the host (79,80). More interestingly, independent of preferential DC infection by chronic pathogens, it has been reported that the functional impairment of DCs is associated with the exhaustion of T cell function and progression of disease during HIV, HBV, HCV, and LCMV infections (81)(82)(83)(84)(85)(86).…”
Section: Extrinsic Factors Regulating T Cell Immunity In a Chronic Anmentioning
confidence: 99%